Teaching-learning process in "Project Management in documentation units": a methodological proposal - Avilés, Rosario Arquero; Cuenca, Gonzalo Marco; Serrano, Silvia Cobo; Simón, L. Fernando Ramos (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
Practical and applied training in project management is conceived as a relevant issue in the teaching-learning process in Library and Information Science for students who will be future professionals in our expertise field. In line with this premise, the design of a Community of Practice (CoP) is presented as methodological and pioneering proposal in the course "Project Management in Documentation Units" within the "Master in Documentation, Library and Archive Management” in the Faculty of Documentation Sciences at Complutense University of Madrid (Spain). Results are analyzed as a consequence of the CoP implementation and from the students’ point of view, who had an active participation in a real training situation.